2015
DOI: 10.1159/000441251
|View full text |Cite
|
Sign up to set email alerts
|

A Participatory Design Approach to Develop a Web-Based Self-Care Program Supporting Early Rehabilitation among Patients after Total Laryngectomy

Abstract: ostomy care, (3) voice prosthesis care, (4) speech rehabilitation, (5) smell rehabilitation, and (6) mobility of head, neck, and shoulder muscles. Expert users expressed concerns regarding tailored exercises, indicated a positive intent to implement the intervention in routine care, and expressed a need for guidance when implementing the intervention. End users and expert users appreciated the content completeness and multimedia-based information built into the application. Conclusion: The participatory design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 32 publications
0
43
0
5
Order By: Relevance
“…Previous research showed that this application is feasible and valued by both patients who undergo total laryngectomy and their care providers. 18,24 Currently, the (cost)effectiveness of the exercise program is being investigated among patients who underwent total laryngectomy. 25 In addition to head and neck cancer and total laryngectomy-specific unmet needs, psychological, physical, and daily living unmet needs were often reported in our study (respectively, 39% and 37% of all patients reported at least 1 low, moderate, or high unmet need).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research showed that this application is feasible and valued by both patients who undergo total laryngectomy and their care providers. 18,24 Currently, the (cost)effectiveness of the exercise program is being investigated among patients who underwent total laryngectomy. 25 In addition to head and neck cancer and total laryngectomy-specific unmet needs, psychological, physical, and daily living unmet needs were often reported in our study (respectively, 39% and 37% of all patients reported at least 1 low, moderate, or high unmet need).…”
Section: Discussionmentioning
confidence: 99%
“…These patients encounter several adjustments in normal daily functioning, which they have to live with for the rest of their lives, including adjustments in airway management, smell, swallowing, and speech. 18 No study has, however, quantitatively investigated the prevalence of unmet supportive care needs among patients treated with total laryngectomy in particular. 14,17 In a focus-group study among patients who underwent total laryngectomy (2-22 years after total laryngectomy surgery), several supportive care needs were identified, including psychosocial care needs and needs related to treatment-related changes in physical functioning, including eating, swallowing, neck and shoulder pain, speech and tracheostomy, and voice prosthesis care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a guided self-help program is expected to be easily accessible for patients and limits burden on time of healthcare providers [ 29 ]. In the first development phase [ 30 ], a needs assessment was performed by means of one focus group in patients and their partners ( n = 9) and four multidisciplinary meetings with healthcare professionals involved in (after)care for patients treated with TL ( n = 11). It was found that a self-help application should not only include an exercise program, but also information modules comprising of daily care for the tracheostomy or voice prosthesis, nutrition, smelling and speech quality.…”
Section: Introductionmentioning
confidence: 99%
“…In the second phase [ 30 ], a prototype of the newly developed self-help application, including an exercise program and self-care education program (i.e. information modules) was developed.…”
Section: Introductionmentioning
confidence: 99%